EXPLORING STUDENTS’ ACADEMIC ACHIEVEMENTS IN ELECTRICITY AND MAGNETISM THROUGH LEARNING STYLES AND LEARNING STYLE-BASED INSTRUCTIONAL STRATEGIES IN MTHATHA HIGH SCHOOLS - Danso, Sakyiwaa; Mushayikwa, Emmanuel (Proceedings of the International Conference on Education, 2017)
Recent studies of the teaching and learning process have shown that learners tend to receive and process information in different ways. This study was conducted to explore the impact of matching instructional strategies to the learners learning styles, considering their cultural background in the teaching of Electricity and Magnetism among Grade 11 physical science learners in schools around Mthatha. To achieve the intended objective and to answer the research question “what impact does the learners‟ learning style preferences have on learners‟ academic achievements”, a total of 205 physical science learners were sampled for the study. A purposive convenience sampling technique was used to select four schools from the target population. A non-experimental quantitative exploratory design was adopted for the study. Physical Science Achievement Test and Index of Learning Style Questionnaire were the main instruments used for gathering the data. Data were analysed using descriptive statistics and inferential statistics including an independent sample ttest together with multiple regression analysis. The result indicates that, the four learning style categories combined did not contribute significantly to the academic achievement of the grade 11 learners in electricity and magnetism at the four high schools in Mthatha.